PENGARUH PENGGUNAAN MEDIA BERBASIS IT TERHADAP HASIL BELAJAR SISWA SMPN 26 MAKASSAR - Irma Suryani Suryani (Universitas Cokroaminoto Palopo, 2022)
Teachers are required to be able to use and develop digital technology for innovative learning processes. IT-based learning media is one of the solutions offered so that students are not bored in learning. This researc aimed to determine whether there is an effect on the learning outcomes of class VII students of SMPN 26 Makassar on the use of IT-based media. Student learning outcomes data obtained were analyzed by descriptive and inferential statistics. The results of the descriptive analysis showed that the average score of the student’s biology learning outcomes in the control class was 65.10 and the experimental class was 77.66. The data on the results of inferential statistical analysis with t-test were obtained a sig score of 0.000 < α 0.05. So it can be concluded that there is an effect of using learning media based on IT toward the student’s learning outcomes.